Optical Tweezers Exploring Neuroscience - Lenton, Isaac C. D.; Scott, Ethan K.; Rubinsztein-Dunlop, Halina; Favre-Bulle, Itia A. (Frontiers in Bioengineering and Biotechnology, 2020)
Over the past decade, optical tweezers (OT) have been increasingly used in neuroscience for studies of molecules and neuronal dynamics, as well as for the study of model organisms as a whole. Compared to other areas of biology, it has taken much longer for OT to become an established tool in neuroscience. This is, in part, due to the complexity of the brain and the inherent difficulties in trapping individual molecules or manipulating cells located deep within biological tissue. Current advances in OT, as well as parallel developments in imaging and adaptive optics, extend significantly the capabilities of OT. In this review, we describe how OT became an established tool in neuroscience and we elaborate on possible future directions for the field. Rather than covering all applications of OT to neurons or related proteins and molecules, we focus our discussions on studies that provide crucial information to neuroscience, such as neuron dynamics, growth, and communication, as these studies have revealed meaningful information and provide direction for the field into the future.